Estratégias de ensino na promoção à saúde da criança e adolescente autista: revisão integrativa de literatura - Barbosa, Ana Jéssily Camargo (2020)
As the decades advance, science has evolved and a growing increase in diagnoses for Neurodevelopmental Disorders, such as Autistic Spectrum Disorder (ASD), requires a reorganization of the school, which encompasses its pedagogical and technological aspects. This reorganization seeks to promote an inclusive environment, ensuring universal access to education. The school represents a favorable environment for the development of health promotion actions, given this, a concern arises: “What teaching strategies are being used to promote the health of autistic children and adolescents? ”. Therefore, this study consists of an Integrative Literature Review on this topic. Publications from the BIREME, Scielo and PubMed databases were investigated, between 2014 and 2018, with a combination of the descriptors "Autistic Disorder", "Autistic Spectrum Disorder" and "Health Technology", using the connectors "and" and " or ", the filters were still delimited" article "", full text "and studies available in English, Portuguese or Spanish. 876 articles were found in the databases, using the pre-selected descriptors. After reading by peers (experts) and selection according to the inclusion and exclusion criteria, six studies were collected for critical analysis, listing four axes for discussion: I. Intervention, II. Multiprofessional team, III. Family and caregivers and IV. School and teaching material. Studies A1, A5 and A6 present psychosexual support, describing the phases of the protocol developed with adolescents and parents, used through preparation for discussion of the themes, but they do not demonstrate how they were conducted. Studies A3 and A4 transcribe interventions on oral health, the first of which investigates teaching actions developed by teachers, followed by training to develop actions in the school environment; while the A4 offers a video modeling to encourage correct tooth brushing. The A5 study works to promote a healthy lifestyle for children with disabilities through dance and physical activity. All studies, at the same time, investigate the perception of parents about the evolution of their children. Therefore, the inseparable character of the spheres "family", "school" and "multiprofessional team" stands out for the proper development of children with ASD, in which they are represented. Therefore, the inseparable character of the spheres “family”, “school” and “multiprofessional team” stands out for the adequate development of children with ASD, in which representatives of each sphere support each other. In this way, sessions to discuss topics related to health promotion, supported by specialized professionals, followed by the proposal of weekly goals to be achieved, can help the social performance of children or adolescents with ASD.Still, the use of video modeling and other technological modalities, based on the repetition of the action, can encourage the child to reproduce the health behavior. Finally, health promotion through physical activity, especially those in which the child and the family member or caregiver participate, represents an effective method to promote behaviors conducive to health and social development.